Optical forming analysis of functional components manufactured in an orbital forming process - Hetzel, Andreas; Sawodny, Annette; Lechner, Michael; Merklein, Marion (XL. Colloquium on Metal Forming, 2022)
Global challenges like an increased sustainability or reduced carbon dioxide emissions demand for efficient process solutions and innovative products. Functional integration and lightweight design propose one way to meet these challenges, nevertheless resulting in increased component complexity as well as long process chains, bringing conventional manufacturing processes to their limits. The process of orbital forming can be applied to efficiently manufacture functional components with varying sheet thickness, like in gear systems. This process is assigned to Sheet-Bulk Metal Forming (SBMF), featuring multi-dimensional stress and strain states in the sheet metal. In order to increase the forming behaviour, the control of the material flow was identified as major challenge in previous research. Therefore, this contribution focuses on the optical forming analysis of the functional components, to increase the understanding regarding the cause-effect relations on the indicated material flow. The components are manufactured out of the high-strength tempered steel 51CrV4 with an initial sheet thickness of 2.0 mm and feature different rotational and cyclic-symmetric elements. The aim of this investigation is the establishment of an extended process understanding on the interdependencies between an occurring three-dimensional material flow and the forming in the context of SBMF processes, in order to increase formability and quality of the manufactured parts.<br
Keywords: sheet-bulk metal forming; orbital forming; forming analysis; sheet metal; functional component